New Florida Foliage Plant Cultivar: Aglaonema ‘Leprechaun’ - Richard J. Henny; Jianjun Chen (EDIS)
This dwarf, more highly branched and rounder cultivar of Aglaonema 'Silver Bay' developed as a whole-stem mutation that was found within a large population of Aglaonema 'Silver Bay' plants. This 4-page fact sheet was written by R. J. Henny and J. Chen, and published by the UF Department of Environmental Horticulture, August 2011.